2011
DOI: 10.1007/s00259-011-1785-1
|View full text |Cite
|
Sign up to set email alerts
|

What is the most accurate whole-body imaging modality for assessment of local and distant recurrent disease in colorectal cancer? A meta-analysis

Abstract: PurposeThe objective of this study was to compare the diagnostic performance of positron emission tomography (PET), PET/CT, CT and MRI as whole-body imaging modalities for the detection of local and/or distant recurrent disease in colorectal cancer (CRC) patients who have a (high) suspicion of recurrent disease, based on clinical findings or rise in carcinoembryonic antigen (CEA).MethodsA meta-analysis was undertaken. PubMed and Embase were searched for studies on the accuracy of whole-body imaging for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 66 publications
0
34
0
8
Order By: Relevance
“…Among 319 patients with relevant information in the current series, 195 (61.1 %) actually had solitary metastases. One should note, however, that the number of nodules can differ, depending on the type of imaging studies used [24,25]. Because most institutions needed more than a decade to accumulate 15 patients or more, there should have been much difference in the potential of imaging modalities at the beginning and the end of the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Among 319 patients with relevant information in the current series, 195 (61.1 %) actually had solitary metastases. One should note, however, that the number of nodules can differ, depending on the type of imaging studies used [24,25]. Because most institutions needed more than a decade to accumulate 15 patients or more, there should have been much difference in the potential of imaging modalities at the beginning and the end of the study period.…”
Section: Resultsmentioning
confidence: 99%
“…In the follow-up of colorectal cancers, 18 F-FDG PET/CT has been shown to have good diagnostic accuracy, has an impact in patient management, and predicts prognosis (3)(4)(5)(6)(7)(8). Although 18 F-FDG PET/CT has not been recommended in the routine follow-up of colorectal cancer, studies have shown that PET/CT is superior to conventional imaging methods in the follow-up (9)(10)(11).…”
mentioning
confidence: 99%
“…When using PET/CT machines, lesion characterization in the CT portion of a PET/CT study increases the specificity of PET/ CT reporting, especially for lesions with moderate and marked FDG uptake. Accordingly, using combined FDG PET/CT imaging for the purpose of tumor recurrence detection in CRC patients with rising CEA levels, specificity proved significantly better when compared to standalone FDG PET imaging with reported figures varying from 92 to 96 % as evidenced by a more recent metaanalysis [49]. Overall, PET/CT allows detection of tumor recurrence in CRC patients with rising CEA levels with an overall sensitivity and specificity of 95 %.…”
Section: Colorectal Cancermentioning
confidence: 93%
“…For this purpose, CT has both a low sensitivity and specificity [49]. While MRI performs better in differentiating local recurrence from scar tissue when compared to CT, limitations still exist in terms of specificity and in the size of tumor detectability [50].…”
Section: Colorectal Cancermentioning
confidence: 99%